ANALISIS LAPORAN ARUS KAS UNTUK MENGUKUR LIKUIDITAS PADA PT. BTPN, TBK - BELLA KRISTI LALUJAN; LUCKY F. TAMENGKEL; HENNY S. TARORE (Universitas Sam Ratulangi, 2016)
ABSTRACT : This study aims to determine the level of liquidity in the PT. BTPN, Tbk. This research uses descriptive quantitative method. The data used in this study according to the secondary data source. The data collected were then analyzed using the ratio of cash flow statement is the ratio of operating cash flow, cash on interest coverage ratio, coverage ratio of cash to current liabilities, and cash flow adequacy ratio, using measurements that trend analysis. The results of this study were presented as follows: in analyzing the cash flow statement at PT. BTPN viewable Operating Cash Flow greater than the Interest Coverage Cash and cash coverage of the current debt. Operating Cash Flow amounted to 56.32%, 1.644% Coverage of cash interest, and to CKHL 37,42%. Thus the liquidity of the company is in a good position, especially when measured by the ratio of AKO, compared with a ratio of CKB and CKHL. Activities of the company are sourced from the cash flow of operating, investing and financing allocated to the business activities are in real terms for the purpose of creating profits. Keywords: Statement of Cash Flows, Liquidity, BTPN